"Just say you’re sorry": avoidance and revenge behavior in response to organizations apologizing for fraud - Wynes, Michael J. (Journal of business ethics, 2022)
Using two experiments, I examine how apologizing for fraud influences investor's avoidance (selling shares) and revenge (litigation) behavior. Investors in experiment one report how many shares they would sell and how likely they would be to pursue legal punishment after discovering fraud has occurred in an organization they are currently invested in and subsequently reading about management's response to the fraud. I manipulate the nature of fraud as fraudulent financial reporting (misreporting) or asset misappropriation (embezzlement). I also manipulate whether management apologizes, scapegoats responsibility, or remains silent after the fraud. Results show avoidance and revenge behavior is more negative after misreporting fraud. Data suggest that this difference may be partially attributable to the underlying moral norm that is violated. Specifically, misreporting is primarily a moral violation of deception, whereas embezzlement is primarily a moral violation of stealing. Results also show differential investor reactions depending on the type of fraud and management's response. For misreporting, revenge behavior is higher when management apologizes, but there is no effect on avoidance behavior. For embezzlement, avoidance behavior is reduced when the organization apologizes, but revenge behavior is unaffected. In experiment two, I replicate the misreporting condition from experiment one and manipulate apology sincerity. Results show that apology sincerity is positively associated with revenge behavior. Results of these two experiments extend both accounting and trust repair research by emphasizing the importance of disentangling moral integrity-based trust violations and that the adage of "just say you're sorry" is helpful in some situations and harmful in others.